Oral comprehensive exam paper on Guoco Securities (Phils.), Inc. - Anzures, Joselito G. (Animo Repository, 1999)
Guoco Securities (Philippines), Inc. was incorporated in October 1987 as Dao Heng (Phil.), Inc. to engage in stock brokerage operations. In June 1992, a change in corporate name was effected to reflect the new name assumed by its Hong Kong-based parent company, the Guoco Group Ltd. of Hong Kong. The Philippine Stock Exchange (PSE) was formed in March 1993, the members of the Manila and Makati Stock Exchanges organized themselves into the PSE and agreed on a functional unification of the two trading floors, thus, allowing a multi-ssited stock exchange linked up via computer. The last decade has seen vast improvements in the Philippines stock market. Much of the growth can be attributed to the functional merger of the two floors and the computerization of trading which started shortly before the unification. The Philippine market has had a lot of ups and downs this decade. It has reached unprecedented hihgs during the early nineties, and lows during the height of the Asian crisis. Guoco Securities has not been spared byu these events. A lot of brokerages closed due to the crisis where we saw the Peso at an all time low of P45 to a Dollar. The fact that Guoco is in business and has a strong presence at that, is a statement to the kind of management it has. It has been able to adapt and adjust to the present situation. At the moment, Guoco is among the top ten brokerages in the Philippines in the volume generated in trading. Since Guoco has been able to remain strong in this business, it is best that it just maintain the status quo. As the saying goes don't fix if it ain't broke. The company should just be aware of the available technology evolving around the business and the new trends that are coming up. Such a trend is the trading via the interet, Guoco should explore the possibilities of such system. Overall, Guoco's success like all the other brokerages, will be very dependent on the kind of stock market we'll have. When we were at the peak of the crisis, there was not much any one can do except to weather out the storm. The years when the company didn't do well were the years when the years that the market didn't do well. The stock market business is a very peculiar business, nobody reallt knows what'll happen. We can only do so much to eliminate the guess work and put the odds on our side.